Implementasi Konsep Smart Goal Setting Pada Bisnis M-Prod Demi Meningkatkan Business Value - Mohamad Hadi Prasetyo (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2023)
Increasing business value for MSMEs is no less important. This community service is carried out with the aim of increasing the business value of M-Prod SMEs which is engaged in convection services. The SMART Goal Setting concept is implemented to make M-Prod have added value and can improve its business performance in the future. This community service program takes the form of a tiered workshop with assistance to the MSMEs concerned so that they focus on profit, not just turnover. This community service is one of the efforts to increase the competitiveness of M-Prod SMEs in order to gain a competitive advantage. The problem faced by business actors is that the specific goals of a business are not measurable. Finally partners do not understand how goals are set and how to analyze a measurable goal. This is very influential in terms of business development, this will have an impact on profits.